Uji korelasi leukosit esterase dan nitrit dengan kultur urin pada infeksi saluran kemih - Ursula Nauli Malau; Purwanto Adipireno (Intisari Sains Medis, 2019)
Background: Urinary tract infection (UTI) is a condition where the urinary tract is infected by pathogens, causing microorganisms in urine. The gold standard examination for UTI is urine culture. Urine culture has some weaknessess. It takes around two days to get result and requires quite expensive cost. Leukocyte esterase and nitrite are relatively inexpensive, less-time consuming and easy to do laboratory tests that can detect UTI.Aim: To explore the correlation of leukocyte esterase and nitrite with urine culture in UTI patients.Methods: A cross sectional study of 42 UTI adult patients which treated at Dr. Kariadi hospital Semarang in September until October 2018. Combur dipstick using colorimetry method and urine culture using convensional method. Correlation test analyze using contingency coefficient.Results: The correlation analysis showed there was a positive correlation between urine esterase leukocytes with urine culture (p = 0.044 and r = 0.152) and there was no correlation between urine nitrite with urine culture (p = 0.272),.Conclusion: There was a correlation between urine leukocyte esterase and urine culture and there was no correlation between the urine nitrite to urine culture. However further researches are needed to analyze factors that affecting the UTI diagnostic.